Encyclopedia of philosophers on religion - Verkamp, Bernard J. (Bernard Joseph), 1938- (Jefferson, N.C. : McFarland & Co., Inc., Publishers, 2008)
"This book addresses and examines the religious affiliations and beliefs of prominent contemporary philosophers. The author profiles 150 such philosophers in separate, alphabetically-ordered entries, providing biographical information, religious upbringing, practice, and beliefs"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Philosophers -- Biography -- Encyclopedias; Religion -- Philosophy -- Encyclopedias